2008
DOI: 10.1108/00251740810919986
|View full text |Cite
|
Sign up to set email alerts
|

Creation and categorization of knowledge in automotive components SMEs in India

Abstract: Purpose -New knowledge creation has gained currency in the global knowledge economy. It is important not only for big firms, but for small and medium size enterprises (SMEs) also. Indian automotive components sector is one of the fastest growing sectors of Indian economy and is dominated by SMEs. This research work aims to study the knowledge creation and categorization in SMEs in Indian automotive components sector. Design/methodology/approach -This paper uses a survey method to collect primary data to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 39 publications
0
46
0
6
Order By: Relevance
“…In that sense, governance appears to be as important as geographical proximity when knowledge diffusion and creation are at stake -possibly even more important (Alberti, 2001). In the same vein, studying the creation and categorization of knowledge management in automotive components SMEs in India, Pillania (2008Pillania ( , p. 1460 concluded that "government and industry associations play an important role in creating the eco-system for new knowledge creation among SMEs".…”
Section: Proximity and Localized Learning Effects In Small Firm Clustersmentioning
confidence: 99%
See 4 more Smart Citations
“…In that sense, governance appears to be as important as geographical proximity when knowledge diffusion and creation are at stake -possibly even more important (Alberti, 2001). In the same vein, studying the creation and categorization of knowledge management in automotive components SMEs in India, Pillania (2008Pillania ( , p. 1460 concluded that "government and industry associations play an important role in creating the eco-system for new knowledge creation among SMEs".…”
Section: Proximity and Localized Learning Effects In Small Firm Clustersmentioning
confidence: 99%
“…Studies on small firms highlight that they often adopt individualistic behaviours to access scarce resources, such as labour, capital or services (Maskell & Lorenzen, 2004). Their lack of managerial skill and cognitive resources limits their ability to perceive opportunities for collaboration (Hewitt-Dundas, 2006;Pillania, 2008). Moreover, they are unable to use external sources to generate new knowledge and innovation, even though these external resources are fundamental to them as they represent the greater part of their knowledge renewal (De Jong & Marsili, 2006;Freel & Harrison, 2006;Pillania, 2008).…”
Section: Proximity and Localized Learning Effects In Small Firm Clustersmentioning
confidence: 99%
See 3 more Smart Citations